2013
DOI: 10.1589/jpts.25.1579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dual Task Training with Visual Restriction and an Unstable Base on the Balance and Attention of Stroke Patients

Abstract: [Purpose] The purpose of this study was to examine the effects of the visual restriction and unstable base dual-task training (VUDT), the visual restriction dual-task training (VDT), and the unstable base dual-task training (UDT) on the balance and attention of chronic stroke patients. [Subjects and Methods] The subjects were 38 chronic stroke patients, who were divided into two groups of 13 patients each and one group of 12 patients. They were given dual-task training for 30 minutes per session, three times a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Eight studies under this category analyzed the effects of dual-task training on postural stability, whereas four studies, in two different categories, were included in the meta-analysis 35,48,61,62. From the nonincluded studies, one study analyzed the effects of dual-task training on subacute stroke patients,34 two studies analyzed the effects on elderly participants,36,63 and one study on younger participants 64.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight studies under this category analyzed the effects of dual-task training on postural stability, whereas four studies, in two different categories, were included in the meta-analysis 35,48,61,62. From the nonincluded studies, one study analyzed the effects of dual-task training on subacute stroke patients,34 two studies analyzed the effects on elderly participants,36,63 and one study on younger participants 64.…”
Section: Resultsmentioning
confidence: 99%
“…The review observed beneficial effects of dual-task training in studies analyzing patients affected from sub-acute34 and chronic stroke 48,62. The studies reported patients affected from stroke to possess considerable impairments in their cognitive–motor domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have reported the relationship between balance and dual-task performance in older adults or persons with neurological diseases [16][17][18][19]. McCulloch et al [19] studied to examine the relationship between postural stability, attention, and dual-task performance in those with acquired brain injury.…”
Section: Discussionmentioning
confidence: 99%